Exploring the Service Providers' and Former Service Users' Perceptions of the Effect and Impact of Living Hope Community Based Substance Abuse Rehabilitation of South Peninsula, Cape Town - Klaas, Portia Siphokazi (Department of Public Health and Family Medicine, 2025)
Substance use remains a significant global public health challenge. This growing issue has extensive consequences, impacting health, crime, exacerbating socio-economic issues, and the spread of HIV/AIDS. In South Africa, the prevalence of substance use, involving alcohol, cocaine, and dagga, is a major concern. The Western Cape, particularly in Cape Town, struggles with unique challenges, marked by prevalent usage of methamphetamine, heroin, and alcohol. Understanding the effectiveness and impact of substance use care is one of the strongest interpreters of improved results among people living with substance use disorders. This study examined providers' and former users' experiences and perspectives on the effect and impact of Living Hope substance use program. Semi-structured interviews were conducted by the researcher and a thematic analysis was used on the interview data. The interviews were conducted with 11 participants, 7 being former users and 4 service providers at Living Hope facilities. Participants shared their perceptions on the effects and impacts of the Living Hope program. Four major themes identified include: Program Effectiveness and Impact, Family and Community Involvement, Enablers/Facilitators and Barriers of the Program, as well as Challenges and Needs of the Program. All participants provided insights into the complex dynamics of addiction treatment. Successes and challenges highlight the necessity of tailored interventions, continuous support, and systemic improvements for program effectiveness. The findings emphasized the diverse nature of addiction recovery, advocating for holistic, resource- backed strategies to address individual and structural aspects for favorable outcomes. The results indicated that a key impact of Living Hope should be in helping former service users in securing jobs after overcoming substance use disorders, as they find it difficult to get employment.